Efficacy of terbinafine and itraconazole in different doses and in combination in the treatment of tinea infection: A randomized controlled parallel group open labeled trial with clinico-mycological correlation - Satyendra K Singh; Najuma Subba; Ragini Tilak (Wolters Kluwer Medknow Publications, 2020)
Background: There is a rising prevalence of dermatophyte infection especially in the tropics. It has been observed that the antifungals are not as effective as they used to be. Aims: To determine the effectiveness of terbinafine and itraconazole in different doses and in combination in the treatment of tinea infection. Materials and Methods: Study design was a randomized parallel group trial. Patients were randomly divided into five parallel arms in which two of the standard drugs in recommended doses were compared with their double doses and with combination of both the drugs. Patients were followed up every 2 weeks. Outcomes were assessed at 4 and 8 weeks. Cure was considered as complete clinical resolution of the lesions. Fungal culture and sensitivity were done by disk diffusion method for all patients. Parametric one-way analysis of variance (F test) and Chi-square test were used for the analysis. Results: Two-hundred seventy-five patients were included in the study. Itraconazole containing groups showed significantly higher cure rates than terbinafine only groups both at 4 and 8 weeks (P < 0.001). Itraconazole containing groups, when compared against each other, were not found to be significantly different. The outcomes between terbinafine only groups were also not significantly different. Cure rates at 8 weeks were found to be greater than that at 4 weeks for all groups which were found to be highly significant (P < 0.001). Conclusions: Itraconazole seems to be more effective than terbinafine. There is no benefit in increasing the dose or using a combination regimen in the treatment of tinea. Prolonged duration of treatment is required for complete cure.